Linguistic style and gender match in funding intention towards crowdfunding project. Issue 3 (23rd June 2021) - Wan Mohamad Nazarie, Wan Nur Fazni; Williams, Russell
Abstract : Purpose: The study aims to explore language style and gender match as a key part of initial trust among potential donors and how this leads to funding success based on the similarity attraction and homophily theories. Empirical analyses of 160 respondents revealed that people are more concerned about "how it is written" (language style) than "who has written it" (gender). Design/methodology/approach: Crowdfunding (CF) is an internet-based method of funding employed by project founders, allowing individuals to raise funds from the crowd to support their projects. It is important for project founders to attract the crowd's interest as potential funders commonly have limited information about projects. One of the early cues about a project that can be picked up by the crowd in CF projects is the text description of the proposal. This text description is crucial for giving the crowd an understanding of the project and for promoting the crowd's trust in the founder, encouraging them to fund the CF project. Based on the similarity attraction and homophily theories, this study sets out to explore language style and gender match as key elements of initial trust among potential donors and how they lead to funding success. A 2 × 2 factorial experimental design (e.g. subject, male and female, × male language style and female language style) was used for the study. To determine the sample size of the experiment, this study applied power and sample size estimations to measure how many respondents were needed for the experiment. Based on the power table of effect size, 128 respondents were considered to be a sufficient number for this experiment to ensure sufficient statistical power of 0.8 and a significance level of 0.05. This study fulfilled the requirement by recruiting 160 respondents, which corresponded to 40 subjects per group based on a 2 × 2 factorial design (the respondents' gender, male and female, and text language style, male and female). The empirical analysis of 160 respondents revealed that people are more concerned about "how it is written" (language style) than "who has written it" (gender). Findings: This paper contributes to project founders' understanding and knowledge of the importance of linguistic style, which can determine the success of a CF project. One of the important results of this study is that the crowd can identify the author's gender based on their writing style. Through an experiment applying factorial analysis (2 × 2), it was found that people are more concerned about "how it is written" (language style) than with "who it is written by" (gender). This means that the project founder, if they know who their audience is, should know how to write the project proposal so that it fits the audience's preferences. More specifically, the success rate of CF projects can be increased by integrating suitable word dimensions in promotions of projects on CF platforms. Therefore, it can be argued that linguistic style is a powerful agent for building a connection with a target audience. The findings of this study can be used as theoretical guidance, and eventually, the potential antecedents of funding intention can be further explored. Research limitations/implications: This study is subject to several limitations. The result is limited to donation-based CF. As this study focuses on the language style of project founders when they describe their CF projects, donation-based CF was the most appropriate platform for this research. In donation-based CF, the style words are more emotion-based, compared to other CF platforms. The experiment, however, could also be replicated for other CF types such as reward-based CF. One important part of CF projects is persuading the crowd to fund them. It is worth mentioning that reward-based CF involves individuals pledging to a business in exchange for a reward. Yet, even though reward-based CF offers rewards, it is generally considered a subset of donation-based CF because there is no financial return to the backer. Therefore, it is suggested that future research should also consider case studies in reward-based CF. Second, from the persuading perspective, this study focusses on narrative language style only, as it facilitates the crowd's understanding of a CF project. Future study can further focus on other information content such as videos in the project proposal. Prior research has found that providing a video in a CF project increases the crowd's confidence in funding (Mitra, 2012). The study is also supported by previous studies that suggest producing a higher quality of video in the project proposal positively related to the success of CF projects (Mollick (2014)). Practical implications: The result of this study empirically confirmed that the crowd's willingness to fund a project proposal and their trust are dependent on the text description of the project proposal. The project founders need to know how to describe the content of a project so that it signals the quality of the project, especially in early start-ups. In other words, the way that a project is created and published through a CF platform will send a valuable signal to the potential donors about the project, and they will either find it acceptable or reject it. If the project appears to lack demand among potential donors, it is easier for project founders to quickly identify that the project will fail, without the need to invest additional capital. Social implications: The findings of this study have important social implications that provide guidelines for project founders on establishing a strategy to help the crowd understand their projects. At the same time, the findings can help the crowd to make their funding decisions. First, the text language used in the CF project by the project founder plays an important role in presenting the campaign and all the ideas need to be presented in a clear way so that the crowd understands the project. In CF projects, pitch is everything (Varsamis, 2018). The pitch refers to the text or video that is provided by the project founder to show their project proposal to the crowd. Compared with traditional funding channels (such as venture capital, i.e. banks), CF is more convenient for raising funds. This is because the project founders need to show their ideas in a creative way to the crowd online, rather than preparing a complex plan and racking their brains on how they can persuade investors to participate (Wang and Yang (2019)). This research intends to help project founders understand how they can influence the crowd by improving the text language used in their CF projects. Originality/value: This paper fulfils an identified need to study how the linguistic style of the project founder would lead to the success rate of crowdfunding projects.